1964
DOI: 10.1037/h0042551
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of student evaluations of teaching.

Abstract: Two groups of students in introductory psychology (691 in the fall semester and 569 in the spring semester) rated their teachers on a 46item questionnaire, derived largely from factor analyses of 145 items that had been used in previous studies elsewhere. The results were factor analyzed separately by sex and semester, and factor similarities obtained by Kaiser's method. 6 factors appeared which were consistent over the 2 administrations, in different semesters, with different students, and teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
3

Year Published

1970
1970
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 6 publications
3
56
0
3
Order By: Relevance
“…Most of the student rating forms generated were validated by using this approach (Costin et al, 1971). Statistical tools like factor analysis have also been used to verify subjectively determined dimensions of the instructional setting and process (Bendig, 1954;Deshpande et al, 1970;Doyle and Whitely, 1974;Hildebrand et al, 1971;Isaacson et al, 1964). Both statistical (factor analysis) and subjective expert judgments were used in generating the items and subscales that make up the CEQ and CIEQ forms (Aleamoni, 1978).…”
Section: Validity Of Student Ratings and Rating Instrumentsmentioning
confidence: 99%
“…Most of the student rating forms generated were validated by using this approach (Costin et al, 1971). Statistical tools like factor analysis have also been used to verify subjectively determined dimensions of the instructional setting and process (Bendig, 1954;Deshpande et al, 1970;Doyle and Whitely, 1974;Hildebrand et al, 1971;Isaacson et al, 1964). Both statistical (factor analysis) and subjective expert judgments were used in generating the items and subscales that make up the CEQ and CIEQ forms (Aleamoni, 1978).…”
Section: Validity Of Student Ratings and Rating Instrumentsmentioning
confidence: 99%
“…There is a significant amount of research demonstrating that students evaluate classroom practices differently than professional observers (Centra, 1993;Isaacson et al, 1964;Simpson & Siguaw, 2000;Sojka, Gupta, & Deeter-Schmelz, 2002). We believe our findings suggest that student self-reported data are a valid alternative for rating the level of engagement and student-centeredness of a course but do not argue for equivalence beyond the measured domains (Schunk & Meece, 1992).…”
Section: Discussionmentioning
confidence: 63%
“…Instructor behavior was measured by the revised McKeachie-'Lin Student Opinion Questionnaire (SOQ) fully described by Isaacson et al, (1963), Isaacson et al (1964), and by Pambookian (1974).…”
Section: Instrumentmentioning
confidence: 99%
“…In forming the three types of instructors, only the discrepancy scores on the evaluative items of skill and rapport were taken into consideration, as research (Isaacson et al, 1964;McKeachie et al, 1971) has shown these dimensions gave evidence of effective teaching. The types were (a) the unfavorably discrepant instructors (UD; instructor rating better than students, N=2), (b) the minimally discrepant instructors (MD; instructor rating as good as students, N=2), and (c) the favorably discrepant instructors (FD; student ratings better than instructor, N=9).…”
mentioning
confidence: 99%